State of normality: Transnational migrants' shifting views of state institutions and their obligations. (March 2021) - Nowicka, Magdalena
The power of nationalism is evident in how people perceive the world around them as 'normal'. A national normality is constituted through education and media but also in everyday encounters with the state or state-regulated institutions in the fields of education, welfare provisions, medical care, finance and others. When people migrate between countries, their sense of 'normality' can become disturbed. Migration might impact how people think of their relationship to the state and its institutions. This article is based on analysis of 120 interviews with Polish migrants in the UK and Germany. It asks if migration creates a 'post-national situation' in which national categories are questioned and negotiated anew. The contexts of Poland, which is undergoing a return to conservative national identity, the UK and its struggle over Brexit, and Germany in its claim to European leadership, provide an instructive case for the discussion of intersections between nationalism and post-nationalism.